Precision risk-based screening might maximize benefit and minimize harm. Issue 11 (November 2018) - Esserman, Laura; LaCroix, Andrea
Population-based mammographic screening is widely accepted as an intervention to reduce overall mortality from breast cancer, but at the cost of morbidity due to false positives and substantial overdiagnosis and overtreatment of ultra-low-risk disease, as well as personal and health-economic burdens. Recent data from a modelling study strengthen the rationale for personalized, risk-based screening approaches, now being tested in multiple clinical trials.